UPAYA MENINGKATKAN HASIL BELAJAR TEMA 3 SUBTEMA 2 MELALUI MODEL PROBLEM BASED LEARNING DI KELAS IV SD NEGERI 200207 SITAMIANG PADANGSIDIMPUAN - Situmorang, Afriani; Zulfadli, Zulfadli; Sucahyo, Eko; Samakmur, Samakmur (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This research aims to see improvements in student learning outcomes for theme 3 subteme 2 diversity of living creatures in the environment. This research uses the Problem Based Learning (PBL) model. The subjucts in this research were all fourth grade students at SDNegeri 200207 sitamiang padangsidimpuan consisting of 22 students. The data collection instruments were observation and test. The results of the research in cycl l,the average student score was 31.81 and in cycl l the average score increased to 72.72. Then, it can be seen from the increase in scores on the theacher observation sheet in cycle 1 of 68.75% and in cycle ll of 85.41%, an increase of 16.66%. judgeng from the increase in scores obtained on student observation sheets in cycle l by 60% and in cycle ll by 75%, there was an increase of 15%. Student learning results have increased. It can be seen that in cycle l, the percentage obtained was 31.81% completed and 68.18%. the % incomplete increased in cycle ll, resulting in a percentage of 72.72%  completed and 27.27% incomplete. The conclusion obtained is that there is an increase in learning outcomes for theme subteme 2 caring about living things using the Problem Based Learning (PBL) model for class IV SD Negeri 200207 Padangsidimpuan.